A multicolor tunable fiber with core–multishell structure by electroluminescence-thermochromic mixing. Issue 35 (7th September 2022) - Zou, Jiahao; Xie, Xinyi; Zhou, Zhe; Dong, Xuemei; Wu, Yueyue; Zhang, Dengfeng; Wang, Min; Chen, Chen; Xiu, Fei; Liu, Juqing
Abstract : A multicolor tunable fiber is realized by synergistically controlling the electroluminescence and thermochromic process. Abstract : Integrating multiple functions into a single fibrous device that can fulfill the requirements of next-generation smart textiles is highly desirable. Herein, we report a multicolor tunable fiber-shaped optoelectronic device that can operate in electroluminescence mode and thermochromic mode separately or simultaneously. This core–multishell structural fiber consists of two silver nanowire conductive shells, an intervening electroluminescent layer, an outermost thermochromic layer and an innermost flexible polymer skeleton. The fiber presents bright, omnidirectional and uniform yellow light emission with the merits of outstanding flexibility and tunable intensity in the AC electric field. Upon the application of a DC bias, the fibrous device temperature varied, further resulting in a color change in the outmost thermochromic layer. Impressively, the charming multicolor emission (up to six colors) could be dynamically achieved by operating the device in both modes, indicating an appealing color-variable display.